High-strength low-modulus antibacterial alloy as well as preparation method and application thereof
By optimizing the composition and process of biomedical alloys, high-strength, low-modulus antibacterial alloys are formed, which solves the shortcomings of traditional materials in terms of mechanical properties and antibacterial properties, and achieves the efficient antibacterial and good mechanical properties of the alloys.
Patent Information
- Application Number
- CN202510357619.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-05-09
AI Technical Summary
Traditional biomedical materials have shortcomings in mechanical properties and antibacterial properties, resulting in loose implants and infection problems.
A high-strength, low-modulus antibacterial alloy was developed to improve the mechanical properties and antibacterial properties of the alloy by optimizing the component ratio of Ti, Zr, Nb, Ag, Cu, and TiO2, and using vacuum arc preparation, rapid solidification, thermal processing and heat treatment processes.
The alloy is achieved with high strength, low modulus, excellent antibacterial properties and good corrosion resistance, which significantly alleviates the stress occlusion effect and implant infection risk.
Smart Images

Figure CN119956141A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical material preparation technology, specifically to a high-strength, low-modulus antibacterial alloy, its preparation method, and its application. Background Technology
[0002] In the biomedical field, implantable medical devices are widely used for disease treatment and bodily function restoration. Traditional biomedical materials, such as stainless steel and titanium alloys, while possessing high strength, have excessively high modulus, which is incompatible with the mechanical properties of natural human bone. This can easily lead to stress shielding effects, causing problems such as osteoporosis of the surrounding bone tissue and implant loosening. Furthermore, most implants lack antibacterial properties, and implant-related infections are a serious clinical problem, increasing patient suffering and medical costs, and potentially even leading to surgical failure. While some high-strength, low-modulus antibacterial biomedical materials have been reported in the current technology, further improvements are needed in material composition, preparation processes, and performance optimization. Therefore, developing a biomedical material with superior performance and a simpler preparation process has significant theoretical and practical implications. Summary of the Invention
[0003] To address the aforementioned challenges, this invention provides a high-strength, low-modulus antibacterial alloy with the molecular formula Ti. a Zr b Nb c Cu d Ag e O f The subscripts a, b, c, d, e, f represent the atomic percentages of the corresponding alloying elements, 50≤a≤70, 20≤b≤60, 5≤c≤7, 2≤d≤4, 1≤e≤5, 2≤f≤4, and a+b+c+d+e+f=100, with the remainder being unavoidable impurities.
[0004] Preferably, the surface of the high-strength, low-modulus antibacterial alloy is coated with a zinc-strontium three-dimensional mesh coating.
[0005] This invention also provides a method for preparing a high-strength, low-modulus antibacterial alloy, comprising the following steps: Ingredients: Weigh Ti, Zr, Nb, Ag, Cu, and TiO2 according to the set alloy target composition, mix them evenly to obtain smelting raw materials, and ensure that the purity of each element by mass percentage is not less than 99.0%. Vacuum arc preparation of alloy ingots: The raw materials for smelting are placed in a vacuum arc device, a vacuum is drawn, and arc melting is carried out under an argon protective atmosphere. The alloy ingots are then obtained. Solidification preparation of alloy rods: The above alloy ingots are placed in a rapid solidification device, vacuumed and melted under an argon protective atmosphere. After complete melting, they are sprayed into a copper mold and rapidly cooled and solidified within 2-4 minutes to obtain alloy rods. Rapid cooling helps to form a fine grain structure, which improves the hardness and wear resistance of the alloy.
[0006] Hot working: The above alloy bars are placed in a heating device, vacuumed, and heated while rotating under an argon protective atmosphere to ensure uniform heating. The temperature is increased to 950-1050℃ at a rate of 10-20℃ / min, and held at this temperature for 30-60 minutes before being removed for forging and rolling. During this process, the deformation of the alloy bars is controlled at 10-30%. Appropriate heating temperature ensures good plasticity of the alloy during hot working, preventing overheating that could lead to grain growth and reduced strength. Appropriate holding time ensures uniform distribution of the alloy composition while avoiding excessive grain growth. Appropriate deformation refines the grains, improving the alloy's strength and toughness. Heat treatment: The alloy bars that have undergone heat treatment are subjected to solution treatment and aging treatment.
[0007] Preferably, during the vacuum arc melting process for preparing the alloy ingot, the current is set to 50~120A, the melting temperature is 1500~2500℃, the number of melting cycles is 4~5, and the melting time for each cycle is 2~3 minutes. Appropriate current and a higher melting temperature help the alloy components to fully fuse and form a uniform alloy ingot; multiple short melting cycles can reduce the risk of oxidation of the alloy at high temperatures.
[0008] Preferably, the solution treatment steps are as follows: the surface of the above alloy rod is cleaned to ensure that there are no impurities and oxide layers on the surface. The cleaned alloy rod is placed in a solution treatment device and heated to 850-950°C at a heating rate of 30-40°C per hour under an argon protective atmosphere. The heating rate should not be too fast to avoid thermal stress caused by rapid temperature changes. The temperature is maintained at this temperature for 2.5-3.5 hours. The holding time should not be too short to ensure that the solute atoms inside the alloy are fully dissolved into the matrix to form a uniform single-phase solid solution. The holding time should not be too long to avoid grain growth. After the holding time is completed, the alloy rod is allowed to cool naturally.
[0009] Preferably, the aging treatment steps are as follows: the alloy rod that has undergone solution treatment is taken out from the solution treatment device and its surface is cleaned. The cleaned alloy rod is then placed in the aging treatment device and heated to 500-600°C at a heating rate of 10-20°C per hour under an argon protective atmosphere. The temperature is maintained at this temperature for 3.5-4.5 hours. The holding time should not be too short to ensure the formation of precipitated phases inside the alloy, thereby further improving the strength and hardness of the material. After the holding time is completed, the alloy rod is allowed to cool naturally.
[0010] This invention also provides a method for preparing a high-strength, low-modulus antibacterial alloy, comprising the following steps: Ingredients: Weigh Ti, Zr, Nb, Ag, Cu, and TiO2 according to the set alloy target composition, mix them evenly to obtain the smelting raw materials, and ensure that the purity of each element by mass percentage is not less than 99.0%; Vacuum arc preparation of alloy ingots: The above-mentioned smelting raw materials are placed in a vacuum arc device, a vacuum is drawn and arc melting is carried out under an argon protective atmosphere, and the alloy ingots are obtained. Solidification preparation of alloy rods: The above alloy ingots are placed in a rapid solidification device, vacuumed and melted under an argon protective atmosphere. After complete melting, they are sprayed into a copper mold and rapidly cooled and solidified within 2-4 minutes to obtain alloy rods. Hot working: The above alloy bar is placed in a heating device, vacuumed, and heated while rotating under an argon protective atmosphere to ensure uniform heating of the alloy bar. It is heated to 950-1050℃ at a rate of 10-20℃ / min and held at this temperature for 30-60min before being taken out for forging and rolling. During this process, the deformation of the alloy bar is controlled at 10-30%. Heat treatment: The alloy bars that have undergone heat working are subjected to solution treatment and aging treatment; Coating with a zinc-strontium three-dimensional mesh coating: Mix 25-35 parts by weight of 5-30 wt% calcium silicate solution, 5-9 parts by weight of 0.5-5.5 wt% zinc nitrate solution, and 5-11 parts by weight of 0.5-5.5 wt% strontium nitrate solution to form a uniform sol solution. Add 45-65 parts by weight of ethanol to adjust the viscosity and uniformity of the sol solution. Immerse the high-strength, low-modulus antibacterial alloy in the sol solution for 3-5 minutes, then slowly lift it out to allow the sol solution to uniformly cover the surface of the high-strength, low-modulus antibacterial alloy. Allow it to air dry naturally, then place it in a heating device and heat it to 600-800℃ for 1-3 hours. Zinc ions in zinc nitrate solution and strontium ions in strontium nitrate solution form stable chemical bonds with the silicon-oxygen bonds in calcium silicate solution through ion exchange reactions. After high-temperature curing, a stable three-dimensional network structure is formed. This structure increases the contact area between the coating and the alloy surface, improving the adhesion and reducing the risk of coating peeling. It also makes the distribution of zinc and strontium ions more uniform, thus significantly improving the hardness, wear resistance, and antibacterial properties of the alloy surface. The different bactericidal mechanisms of zinc and strontium in the coating and copper and silver in the alloy work synergistically to improve and optimize the antibacterial performance of the alloy, ensuring that it can efficiently and rapidly kill a variety of common pathogens. Zinc ions can disrupt biofilms to enhance the permeability of copper and silver ions; copper and silver ions can interfere with the activity of metabolic enzymes and generate reactive oxygen species; strontium ions can interfere with bacterial calcium signaling pathways, thus forming a multi-target attack on bacteria. The coating and substrate synergistically regulate the ion release rate to ensure long-lasting antibacterial effect.
[0011] Beneficial effects: This technical solution, through composition optimization and process innovation, further optimizes the mechanical properties and antibacterial efficacy of medical alloys. By adding titanium dioxide as a controllable oxygen source, it generates nano-oxides with other components in the alloy under high-temperature conditions. These oxides act as second-phase particles to refine the alloy grains, resulting in a yield strength exceeding 1000 MPa, a fracture strength exceeding 1500 MPa, and an elastic modulus reduced to below 55 GPa, significantly alleviating the stress shielding effect. The oxygen vacancies generated by the thermal decomposition of titanium dioxide promote the continuous release of silver and copper ions. Combined with the photocatalytic activity of titanium dioxide, the antibacterial rate against Staphylococcus aureus reaches 96%. The above-mentioned multi-dimensional innovations employ a dual regulation mechanism of internal oxygen supply (TiO2 thermal decomposition) and external oxygen barrier (vacuum plus argon protection) to stably control the oxygen content in the alloy within the target range, avoiding grain boundary embrittlement and ensuring uniform distribution of oxide strengthening phases. By precisely controlling key process parameters such as heating temperature and heating time during vacuum arc melting, rapid solidification, hot working, and heat treatment, the microstructure of the alloy is effectively controlled, thereby significantly improving the mechanical properties of the alloy. Through the above-mentioned multi-dimensional innovations, a high-strength, low-modulus, and highly efficient antibacterial alloy is obtained, solving the bottleneck problem of traditional alloys being unable to simultaneously achieve mechanical properties and biological functions, and providing a new generation of alloy solutions for medical implantable devices. Attached Figure Description
[0012] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 The images are XRD patterns of the alloys prepared in Examples 1 to 3 of this invention. Detailed Implementation
[0013] To enable those skilled in the art to understand the technical solution of the present invention more clearly, the present invention will be further described in detail below with reference to the embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto.
[0014] Example 1 Preparation of Ti 70 Zr 20 Nb5Cu2Ag1O2 alloy Ingredients: Weigh 3336.42g of elemental titanium, 1842.83g of elemental zirconium, 469.24g of elemental niobium, 128.38g of elemental copper, 108.96g of elemental silver, and 80.68g of titanium dioxide, mix them evenly to obtain the smelting raw material, and the purity of each element by mass percentage shall not be less than 99.0%; Preparation of alloy ingots in a vacuum arc furnace: The raw materials for smelting are placed in a vacuum arc furnace, and a vacuum of 5 × 10⁻⁶ is drawn. -3Pa, argon gas was introduced and electric arc melting was carried out under argon protective atmosphere. The current was set to 50A, the melting temperature was 1500℃, the number of melting times was 4, and the melting time for each time was 2min. The alloy ingot was then taken out. Solidification preparation of alloy bars: Place the alloy ingot in a rapid solidification apparatus and evacuate to a vacuum of 5 × 10⁻⁶. -3 Pa, filled with argon gas and heated to 1500℃ under argon protective atmosphere, after being completely melted, sprayed into a copper mold and rapidly cooled and solidified within 4 minutes to obtain alloy rods; Hot working: The alloy bar is placed in a heating device, vacuumed, and heated while rotating under an argon protective atmosphere at a rate of 10℃ / min to 950℃. After holding at this temperature for 30 minutes, it is taken out for forging and rolling. During this process, the deformation of the alloy bar is controlled within 10%. Heat treatment: The hot-worked alloy bars undergo solution treatment and aging treatment. The solution treatment steps are as follows: the hot-worked alloy bars are surface-cleaned to ensure no impurities or oxide layer. The cleaned alloy bars are placed in a solution treatment apparatus and heated to 850°C at a rate of 30°C per hour under an argon protective atmosphere, and held at this temperature for 2.5 hours. The aging treatment steps are as follows: the solution-treated alloy bars are removed from the solution treatment apparatus and surface-cleaned. The cleaned alloy bars are placed in an aging treatment apparatus and heated to 500°C at a rate of 10°C per hour under an argon protective atmosphere, and held at this temperature for 3.5 hours. After holding at this temperature, the alloy bars are allowed to cool naturally to obtain Ti. 70 Zr 20 Nb5Cu2Ag1O2 alloy.
[0015] Example 2 Preparation of Ti 60 Zr 25 Nb6Cu3Ag3O3 alloy Ingredients: Weigh 2828.73g of elemental titanium, 2303.54g of elemental zirconium, 563.09g of elemental niobium, 192.58g of elemental copper, 326.88g of elemental silver, and 121.02g of titanium dioxide, mix them evenly to obtain the smelting raw material, and the purity of each element by mass percentage shall not be less than 99.0%; Preparation of alloy ingots in a vacuum arc furnace: The raw materials for smelting are placed in a vacuum arc furnace, and a vacuum of 7 × 10⁻⁶ is drawn. -3 Pa, argon gas was introduced and electric arc melting was carried out under argon protective atmosphere. The current was set to 85A, the melting temperature to 2000℃, the melting was carried out 5 times, and the melting time for each time was 3min. The alloy ingot was then taken out. Solidification preparation of alloy bars: Place the alloy ingot in a rapid solidification apparatus and evacuate to a vacuum of 7 × 10⁻⁶. -3Pa, filled with argon gas and heated to 2000℃ under argon protective atmosphere, after complete melting, sprayed into copper mold and rapidly cooled and solidified within 2 minutes to obtain alloy rods; Hot working: The alloy bar is placed in a heating device, vacuumed, and heated while rotating under an argon protective atmosphere at a rate of 15℃ / min to 1000℃. After holding at this temperature for 45 minutes, it is taken out for forging and rolling. During this process, the deformation of the alloy bar is controlled within 20%. Heat treatment: The hot-worked alloy bars undergo solution treatment and aging treatment. The solution treatment steps are as follows: the hot-worked alloy bars are surface-cleaned to ensure no impurities or oxide layer. The cleaned alloy bars are placed in a solution treatment apparatus and heated to 900°C at a rate of 35°C per hour under an argon protective atmosphere, and held at this temperature for 3 hours. The aging treatment steps are as follows: the solution-treated alloy bars are removed from the solution treatment apparatus and surface-cleaned. The cleaned alloy bars are placed in an aging treatment apparatus and heated to 550°C at a rate of 15°C per hour under an argon protective atmosphere, and held at this temperature for 4 hours. After holding at this temperature, the alloy bars are allowed to cool naturally to obtain Ti. 60 Zr 25 Nb6Cu3Ag3O3 alloy.
[0016] Example 3 Preparation of Ti 50 Zr 30 Nb7Cu4Ag5O4 alloy Ingredients: Weigh 2321.03g of elemental titanium, 2764.24g of elemental zirconium, 656.94g of elemental niobium, 256.77g of elemental copper, 544.8g of elemental silver, and 161.35g of titanium dioxide, mix them evenly to obtain the smelting raw material, and the purity of each element by mass percentage shall not be less than 99.0%; Preparation of alloy ingots in a vacuum arc furnace: The raw materials for smelting are placed in a vacuum arc furnace, and a vacuum of 9×10⁻⁶ is drawn. -3 Pa, argon gas was introduced and electric arc melting was carried out under argon protective atmosphere. The current was set to 120A, the melting temperature to 2500℃, the melting was carried out 5 times, and the melting time for each time was 3 minutes. The alloy ingot was then taken out. Solidification preparation of alloy bars: Place the alloy ingot in a rapid solidification apparatus and evacuate to a vacuum of 9 × 10⁻⁶. -3 Pa, filled with argon gas and heated to 2500℃ under argon protective atmosphere, after being completely melted, sprayed into a copper mold and rapidly cooled and solidified within 3 minutes to obtain alloy rods; Hot working: The alloy bar is placed in a heating device, vacuumed, and heated while rotating under an argon protective atmosphere at a rate of 20°C / min to 1050°C. After holding at this temperature for 60 minutes, it is taken out for forging and rolling. During this process, the deformation of the alloy bar is controlled within 30%. Heat treatment: The hot-worked alloy rods undergo solution treatment and aging treatment. The solution treatment steps are as follows: the hot-worked alloy rods are surface-cleaned to ensure no impurities or oxide layer. The cleaned alloy rods are then placed in a solution treatment apparatus and heated to 950°C at a rate of 40°C per hour under an argon protective atmosphere, and held at this temperature for 3.5 hours. The aging treatment steps are as follows: the solution-treated alloy rods are removed from the solution treatment apparatus and surface-cleaned. The cleaned alloy rods are then placed in an aging treatment apparatus and heated to 600°C at a rate of 20°C per hour under an argon protective atmosphere, and held at this temperature for 4.5 hours. After holding at this temperature, the alloy rods are allowed to cool naturally to obtain the prepared Ti. 50 Zr 30 Nb7Cu4Ag5O4 alloy.
[0017] Example 4 The difference between this embodiment and Embodiment 2 is that, based on Embodiment 2, an additional step of coating a three-dimensional zinc-strontium mesh coating is added. Specifically, 25 parts of 5wt% calcium silicate solution, 5 parts of 0.5wt% zinc nitrate solution, and 5 parts of 0.5wt% strontium nitrate solution are mixed evenly to form a uniform sol solution. 45 parts of ethanol are added to adjust the viscosity and uniformity of the sol solution. The high-strength, low-modulus antibacterial alloy is immersed in the sol solution for 3 minutes, then slowly lifted out, allowing the sol solution to evenly cover the surface of the high-strength, low-modulus antibacterial alloy. It is then allowed to air dry naturally, and finally placed in a heating device and heated to 600°C for 1 hour to allow the Ti... 60 Zr 25 A zinc-strontium three-dimensional mesh coating is added to the surface of the Nb6Cu3Ag3O3 alloy.
[0018] Example 5 This embodiment differs from Embodiment 2 in that it adds a zinc-strontium three-dimensional mesh coating process step. Specifically, 30 parts of 17wt% calcium silicate solution, 7 parts of 3wt% zinc nitrate solution, and 8 parts of 3wt% strontium nitrate solution are mixed evenly to form a uniform sol solution. 55 parts of ethanol are added to adjust the viscosity and uniformity of the sol solution. The high-strength, low-modulus antibacterial alloy is immersed in the sol solution for 4 minutes, then slowly lifted out, allowing the sol solution to evenly cover the surface of the high-strength, low-modulus antibacterial alloy. It is then air-dried and placed in a heating device to be heated to 700°C and held at that temperature for 2 hours to allow the Ti... 60 Zr 25A zinc-strontium three-dimensional mesh coating is added to the surface of the Nb6Cu3Ag3O3 alloy.
[0019] Example 6 The difference between this embodiment and Embodiment 2 is that, based on Embodiment 2, an additional step of coating a three-dimensional zinc-strontium mesh coating is added. Specifically, 35 parts of 30wt% calcium silicate solution, 9 parts of 5.5wt% zinc nitrate solution, and 11 parts of 5.5wt% strontium nitrate solution are mixed evenly to form a uniform sol solution. 65 parts of ethanol are added to adjust the viscosity and uniformity of the sol solution. The high-strength, low-modulus antibacterial alloy is immersed in the sol solution for 5 minutes, then slowly lifted out, allowing the sol solution to evenly cover the surface of the high-strength, low-modulus antibacterial alloy. It is then allowed to air dry naturally, and finally placed in a heating device and heated to 800°C for 3 hours to allow the Ti... 60 Zr 25 A zinc-strontium three-dimensional mesh coating is added to the surface of the Nb6Cu3Ag3O3 alloy.
[0020] Comparative Example 1 The difference between this comparative example and Example 2 is that titanium dioxide was not added.
[0021] Comparative Example 2 The difference between this comparative example and Example 2 is that titanium dioxide was not added, and the entire preparation process was carried out in air without vacuuming or argon filling.
[0022] Comparative Example 3 The difference between this comparative example and Example 2 is that, in the solidification preparation of the alloy rod, after it is completely melted, it is sprayed into a copper mold and solidified by natural cooling. In addition, during the hot working process, the deformation of the alloy rod is 35%.
[0023] Test methods X-ray diffraction (XRD) analysis: The X-ray diffractometer used was model D / MAX-2200pc, manufactured by Rigaku, Japan. The target material used was a Cu target (Kα ray wavelength λ=1.5406Å). The sample was fixed in the center of the sample holder using modeling clay. The sample was gently pressed with a glass slide to ensure that the sample surface was on the same horizontal plane as the sample holder. The parameters set were: working voltage 40 kV, working current 40 mA, scanning speed 6° / min, and scanning angle range 20~100°.
[0024] Alloy mechanical property testing method: Quasi-static compression test was conducted on a universal testing machine (SANS5504 50KN model). A 2mm diameter rod-shaped alloy specimen with an aspect ratio of approximately 2:1 was used. Both ends of the specimen were ground parallel to each other and perpendicular to the specimen's axis. Displacement control was employed during the test, and the loading speed was 2.1 × 10⁻⁶. -4 s-1 The yield strength, fracture strength, and elastic modulus are calculated from the obtained stress-strain curves.
[0025] The corrosion resistance test method for the alloy was as follows: Electrochemical tests were performed using an electrochemical workstation, specifically the Princeton Applied Research Model VersaSTAT and VersaSTAT3. A three-electrode system was employed, with the alloy sample as the working electrode (WE), a platinum sheet as the counter electrode (CE), and a saturated calomelelectrode (SCE) as the reference electrode. The solution used was PBS (phosphate buffer solution, NaCl-8.01, KCl-0.20, Na2HPO4-1.15, KH2PO4-0.20, units g / L). The alloy sample, 5 mm in diameter and 2 mm thick, was immersed in the solution until the open circuit potential (OCP) reached a stable state before polarization experiments, including potentiodynamic polarization or cyclic anodic polarization. The potentiodynamic polarization scan started 50 mV below the open circuit potential (OCP -50 mV), and the stop potential was set at 2.0 V. The experiment was manually stopped after pitting corrosion occurred, and the potential scan rate was 50 mV / min.
[0026] Test method for antibacterial effect of alloy: Mix 1.5 × 10⁻⁶ alloys with a concentration of 1.5 × 10⁻⁶. 6 1 ml of Staphylococcus aureus ATCC25923 (S. aureus) bacterial suspension was added to a 24-well plate. A 2 mm diameter, 6 mm long alloy sample was placed into each well of the 24-well plate, completely submerged in the bacterial suspension. The 24-well plate was incubated at 37°C for 24 hours, after which the samples were removed. The bacterial suspension used to submerge the samples in each well was serially diluted with PBS solution (phosphate buffer, NaCl 8.01, KCl 0.20, Na2HPO4 1.15, KH2PO4 0.20, units g / L) at concentrations of 1:100, 1:1000, and 1:10000. 100 μl of the diluted bacterial suspension was added to a nutrient agar plate, spread evenly, and then incubated at 37°C for 24 hours. Visible dispersed colonies grew on the agar plate surface; each single colony represented the original sample. A single bacterium was identified in the sample. The number of colonies in the culture dishes of different samples was recorded using a digital camera, and the inhibition rate was calculated by comparing the results with the negative control group.
[0027] The alloys prepared in Examples 1-6 and Comparative Examples 1-3 were subjected to performance tests according to the above test methods, and the test results are shown in Table 1.
[0028] Table 1 Alloy property test results
[0029] As can be seen from the experimental data in Table 1, the high-strength, low-modulus antibacterial alloy of the present invention exhibits excellent performance in all aspects.
[0030] The alloys in Examples 1-6 all have yield strengths above 1000 MPa, fracture strengths above 1500 MPa, elastic moduli below 55 GPa, antibacterial rates above 96%, and high self-corrosion potentials and pitting potentials. This indicates that the alloys possess high strength, low modulus, excellent antibacterial properties, and good corrosion resistance.
[0031] Comparing Examples 1-3, it is evident that Example 2 exhibits superior performance in all aspects. This may be related to the composition ratios of the various components in the alloy of Example 2 and the settings of the process parameters. Regarding the composition, the atomic percentages of Ti, Zr, Nb, Cu, Ag, and O in Example 2 are 60, 25, 6, 3, 3, and 3, respectively. This ratio facilitates the interaction of the elements and promotes the uniform distribution of the strengthening phase. In terms of process, when preparing alloy ingots in a vacuum electric arc furnace, an 85A current, a melting temperature of 2000℃, five melting cycles, and a melting time of 3 minutes each ensure sufficient fusion of alloy components, reduce component segregation, and guarantee alloy homogeneity. Rapid cooling and solidification within 2 minutes helps to form a finer and more uniform grain structure, and the refined grains can enhance the alloy's strength and toughness. During hot working, heating to 1000℃ at 15℃ / min and holding for 45 minutes, while controlling the deformation amount to 20%, ensures that the alloy has good plasticity for easy forging and rolling, and effectively refines the grains, thereby improving the alloy's strength and toughness. Appropriate parameters for solution treatment and aging treatment allow solute atoms to fully dissolve and precipitates to fully form, further optimizing the alloy's microstructure and improving its overall performance.
[0032] Compared with Example 2, the addition of the zinc-strontium three-dimensional network coating improved the yield strength, fracture strength, self-corrosion potential, pitting potential, and antibacterial rate. This is because the coating forms a stable three-dimensional network structure through ion exchange, which enhances the bonding force with the alloy surface, makes the zinc-strontium ions evenly distributed, and synergistically improves the antibacterial and corrosion resistance of the alloy with copper and silver elements.
[0033] Further analysis of the experimental data revealed that, compared to Example 2, the lack of titanium dioxide in Comparative Example 1 resulted in a decrease in the alloy's yield strength, fracture strength, self-corrosion potential, and pitting potential, while the elastic modulus increased and the antibacterial rate significantly decreased. This is because titanium dioxide, as a controllable oxygen source, generates nano-oxides with other components at high temperatures. These nano-oxides, acting as second-phase particles, are uniformly dispersed in the alloy matrix, refining the grain size. The grain-refining strengthening mechanism further hinders dislocation movement in the alloy, thereby significantly improving its yield strength and fracture strength. Simultaneously, the fine grain structure increases the grain boundary area, effectively reducing the alloy's elastic modulus and making it closer to the mechanical properties of natural human bone, thus reducing stress shielding effects. Furthermore, titanium dioxide possesses photocatalytic activity, generating hydroxyl radicals that disrupt bacterial structures. Additionally, the oxygen vacancies generated by the thermal decomposition of titanium dioxide promote the continuous release of silver and copper ions in the alloy. These two factors synergistically enhance the alloy's antibacterial properties.
[0034] Although Comparative Example 2 showed an uncontrollable oxygen source, leading to a decrease in alloy strength, an increase in modulus, and a decrease in antibacterial rate, it demonstrates that the combination of vacuum and argon protection with a controllable oxygen source is crucial for improving alloy performance. Vacuum and argon can prevent alloy oxidation, ensure the stability of composition and microstructure, and facilitate the effective functioning of the oxygen source.
[0035] Comparative Example 3, which underwent natural cooling during solidification, experienced a 35% deformation during hot working, resulting in a decrease in yield strength, fracture strength, self-corrosion potential, and pitting potential, while increasing the elastic modulus. This is likely because natural cooling, with its slow cooling rate, allows sufficient time for atomic diffusion, enabling grains to engulf each other during growth and ultimately forming coarse grains. These coarse grains reduce the grain boundary area, weakening the resistance of grain boundaries to dislocation movement, thus decreasing the alloy's yield strength and fracture strength. Simultaneously, the coarse grain structure hinders the dispersion of internal stress, making stress concentration more likely under load, further reducing the alloy's mechanical properties. During hot working, excessive deformation exceeds the alloy's reasonable tolerance range, leading to numerous defects and residual stresses within the alloy, reducing its strength and corrosion resistance, and damaging its internal microstructure, thus increasing the elastic modulus. Compared to the commonly used medical titanium alloy Ti-6Al-4V, the alloys in Examples 1-6 exhibit superior yield strength, fracture strength, and antibacterial properties, with a lower elastic modulus, better meeting the mechanical performance requirements of human bones, demonstrating the significant performance advantages of the alloys of this invention.
[0036] In summary, by adding titanium dioxide, using a vacuum and argon-protected preparation process, and coating with a zinc-strontium three-dimensional network coating, the mechanical properties, corrosion resistance, and antibacterial properties of the alloy can be significantly improved.
[0037] The above are merely embodiments of the present invention and are not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principle of the present invention should be included within the scope of the claims of the present invention.
Claims
1. A high-strength, low-modulus antibacterial alloy, characterized in that: The alloy has the molecular formula Ti a Zr b Nb c Cu d Ag e O f , where the subscripts a, b, c, d, e, and f represent the atomic percentages of the corresponding alloying elements, 50≤a≤70, 20≤b≤30, 5≤c≤7, 2≤d≤4, 1≤e≤5, 2≤f≤4, and a+b+c+d+e+f=100, and the remainder is unavoidable impurities.
2. The high-strength, low-modulus antibacterial alloy according to claim 1, characterized in that: The surface of the high-strength and low-modulus antibacterial alloy is coated with a zinc-strontium three-dimensional mesh coating.
3. The method for preparing a high-strength and low-modulus antibacterial alloy according to claim 1, characterized in that: The following steps are involved: Batching: Weigh Ti, Zr, Nb, Ag, Cu, and TiO2 according to the set alloy target composition, mix them evenly to obtain smelting raw materials, and the purity of each element by mass percentage is not less than 99.0%; Preparation of alloy ingots by vacuum arc: placing the smelting raw materials into a vacuum arc device, evacuating the vacuum, and performing arc melting under an argon protective atmosphere, and taking out the alloy ingots; Solidification to prepare alloy rods: placing the alloy ingot in a rapid solidification device, evacuating the device and melting it under an argon protective atmosphere, spray-casting it into a copper mold after it is completely melted, and rapidly cooling and solidifying it within 2 to 4 minutes to obtain the alloy rods; Hot working: placing the alloy bar into a heating device, evacuating the device and rotating and heating the device under an argon protective atmosphere to ensure that the alloy bar is evenly heated, heating the device to 950-1050°C at a rate of 10-20°C / min, and keeping the temperature for 30-60min before taking the device out for forging and rolling. During this process, the deformation of the alloy bar is controlled at 10-30%. Heat treatment: The alloy bar after heat treatment can be subjected to solution treatment and aging treatment.
4. The method for preparing a high-strength and low-modulus antibacterial alloy according to claim 3, characterized in that: In the process of preparing the alloy ingot by vacuum arc, the current is set to 50-120A, the melting temperature is 1500-2500°C, the melting times are 4-5 times, and the melting time for each time is 2-3 minutes.
5. The method for preparing a high-strength, low-modulus antibacterial alloy according to claim 3, characterized in that: The solution treatment steps are as follows: the surface of the alloy rod is cleaned to ensure that there are no impurities and oxide layers on the surface, the cleaned alloy rod is placed in a solution treatment device, and the temperature is increased to 850-950°C at a heating rate of 30-40°C per hour under an argon protective atmosphere. The heating rate should not be too fast to avoid thermal stress caused by rapid temperature changes, and this temperature is maintained for 2.5-3.5 hours. The insulation time cannot be too short to ensure that the solute atoms inside the alloy are fully dissolved into the matrix to form a uniform single-phase solid solution. After the insulation is completed, the alloy rod is allowed to cool naturally.
6. The method for preparing a high-strength, low-modulus antibacterial alloy according to claim 5, characterized in that: The aging treatment steps are as follows: taking out the alloy rod that has undergone solid solution treatment from the solid solution treatment device and cleaning the surface, placing the cleaned alloy rod into the aging treatment device, heating it to 500-600° C. at a heating rate of 10-20° C. per hour under an argon protective atmosphere, and maintaining this temperature for 3.5-4.5 hours. The holding time should not be too short to ensure the formation of precipitation phases inside the alloy, further improve the strength and hardness of the material, and allow the alloy rod to cool naturally after the holding time is completed.
7. The method for preparing a high-strength, low-modulus antibacterial alloy according to claim 2, characterized in that: The following steps are involved: Batching: Weigh Ti, Zr, Nb, Ag, Cu, and TiO2 according to the set alloy target composition, mix them evenly to obtain smelting raw materials, and the purity of each element by mass percentage is not less than 99.0%, and mix them evenly to obtain smelting raw materials; Preparation of alloy ingots by vacuum arc: placing the smelting raw materials into a vacuum arc device, evacuating the vacuum, and performing arc melting under an argon protective atmosphere, and taking out the alloy ingots; Solidification to prepare alloy rods: placing the alloy ingot in a rapid solidification device, evacuating the device and melting it under an argon protective atmosphere, spray-casting it into a copper mold after it is completely melted, and rapidly cooling and solidifying it within 2 to 4 minutes to obtain the alloy rods; Hot working: placing the alloy bar into a heating device, evacuating the device and rotating and heating the device under an argon protective atmosphere to ensure that the alloy bar is evenly heated, heating the device to 950-1050°C at a rate of 10-20°C / min, and keeping the temperature for 30-60min before taking the device out for forging and rolling. During this process, the deformation of the alloy bar is controlled at 10-30%. Heat treatment: subjecting the alloy bar after heat treatment to solid solution treatment and aging treatment; Coating a zinc-strontium three-dimensional mesh coating: mix 25 to 35 parts of a 5 to 30 wt% calcium silicate solution, 5 to 9 parts of a 0.5 to 5.5 wt% zinc nitrate solution, and 5 to 11 parts of a 0.5 to 5.5 wt% strontium nitrate solution in proportion by mass to form a uniform sol solution, add 45 to 65 parts of ethanol to adjust the viscosity and uniformity of the sol solution, immerse the high-strength, low-modulus antibacterial alloy in the sol solution for 3 to 5 minutes, then slowly lift it up so that the sol solution evenly covers the surface of the high-strength, low-modulus antibacterial alloy, air-dry it naturally, and then place it in a heating device and heat it to 600 to 800° C., and keep it warm for 1 to 3 hours.
8. Use of the high-strength, low-modulus antibacterial alloy as claimed in claim 1 in orthopedic or dental materials.
9. Use of the high-strength, low-modulus antibacterial alloy as claimed in claim 2 in orthopedic or dental materials.
10. Use of the high-strength, low-modulus antibacterial alloy obtained by the preparation method according to claim 3 or 7 in orthopedic or dental materials.